Changes in Color of Urine in the Patients on Concoctive (Munzij) Therapy - An Observational Study - Nabila Subhan; Tariq Nadeem Khan; Mohd Nayab (Tehran University of Medical Sciences, 2022)
There are various causes of diseases but retention of morbid matter (mawad-e-fasida) in the body is one of the main causes and these morbid matters must be evacuated from the body to regain health. Concoction (nuḍj) and evacuation (tanqiya) are the two prime methods that ancient physicians described and recommended for the treatment of such diseases. Concoction is a process of moderation and modification in the viscosity of morbid matter to make them suitable for evacuation conveniently from their sites of lodgement. Several indices of concoction can be seen in the pulse, urine, and stool, which help to find out level and stages of concoction. Drugs, which appropriately alter the consistency of morbid matter to render them easily eliminable from the body, are known as concoctive (Munzijat). A total of 125 eligible participants, after getting their written informed consent, were enrolled in the study and 50 participants completed the study. They were advised to take a decoction of phlegmatic concoctive drugs once in the morning before breakfast for 15 days. Three urine samples of each patient were collected: before starting the concoctive therapy, at 5th day and 12th day. The changes in the color intensity of urine were observed by photoelectric colorimeter at a wavelength of 580 nm (yellow filter). The patients were advised to refrain from such diets and drugs which tend to change the color of urine during the entire study period. Statistical analysis was restricted to those patients who completed the study. The Mean ± SD of optical density at 0 day was 0.0872 ± 0.0284; while it was 0.0782 ± 0.0275 at 5th day which was not statistically significant (p > 0.05). The Mean ± SD of optical density on 12th day was 0.0484 ± 0.0196 which was found statistically significant (p < 0.01) in comparison to baseline values. Concoction is a continuous process of medicatrix naturae (tabiyat) which is facilitated by humour specified concoctive drugs. The statistically significant change in urine color indicates the effect of concoctive drugs on body humours.